Hemorrhagic colitis syndrome in children: the etiological structure in the infectious diseases clinic - O. V. Molochkova; O. B. Kovalev; O. V. Shamsheva; A. A. Sakharova; N. V. Sokolova; E. V. Galeeva; A. A. Korsunsky; N. V. Davidenko (LLC "Diagnostics and Vaccines", 2021)
The range of differential diagnostic search in the development of hemorrhagic colitis (hemocolitis) is wide enough and includes infectious and non-infectious factors. Purpose: clinical, laboratory and etiological analysis of bacterial diarrhea occurring with hemorrhagic colitis in the infectious diseases department.Materials and methods: a retrospective study of 141 case histories of those hospitalized in the infectious diseases department of the2 Children's City Clinical Hospital No. 9 named after G.N. Speransky of Moscow in 2019-2021 patients with clinical picture of hemocolitis. Hemocolitis was determined on the basis of macroscopic and microscopic signs (in scatology - mucus, leukocytes, erythrocytes) signs. All patients underwent routine laboratory examinations. The etiology was verified using modern methods of laboratory diagnostics (bacteriological analysis of feces, Latex test, ICA, ELISA, PCR, IHR).Results. There were 137 patients with infectious hemocolitis. Inflammatory bowel disease was diagnosed in 3 children, anus fissure - in 1 child. Young children under 3 years of age prevailed (77%). The etiology of infectious hemocolitis was deciphered in 47 patients (34%). Salmonellosis (36%) and shigellosis (36%) prevailed. Campylobacteriosis, clostridiosis-dificile and klebsiellosis accounted for 11%, 9% and 6% of cases, respectively. Yersiniosis was detected in 1 child at the age of 5 months. The severe form was found in 5.8% of cases, in most cases with shigellosis. Symptoms of intoxication and febrile fever were expressed in all patients, vomiting - in 28.5%, abdominal pain - in 94%, mesenteric adenitis on ultrasound - in 15%, diarrhea with a frequency of more than 5 times a day - in 84%, dehydration - in 64%, intercurrent diseases (ARVI, pneumonia) - in 41.3% of cases. Inflammatory changes in infectious hemocolitis were manifested by an increase in C-reactive protein in 71% (23.91 ± 24.17 mg/l), leukocytosis - in 69% (11.58 ± 3.52 х103 / μl), thrombocytosis - in 26%, an increase in the relative number of stab neutrophils in the general blood test in 78% of cases (10.95 ± 0.4%).Conclusions. Differential diagnostic search in the development of hemocolitis should include modern diagnostic methods, if necessary, additional instrumental studies and specialist consultations to exclude inflammatory bowel diseases.